IDEN TRANSLATOR VS GOOGLE TERJEMAHAN: BIAS GENDER DALAM ALAT BANTU ELEKTRONIK PENERJEMAHAN DALAM JARINGAN - Mochamad Nuruz Zaman (Universitas Negeri Makassar, 2019)
ID <> EN Translator vs Google Translation: Gender Bias in Electronic Translation Tools Online. This study investigates the gender bias expression of the pronoun “dia (pronoun of Indonesia language)” that does not refer yet the absolute gender either man or woman in the translation online tools of android play store. This study was designed descriptive qualitative with purposive sampling. Data collection is done by analyzing documents, namely analyzing data related to gender bias in the object of study. The results showed that negative meanings for men were less than positive. Negative meaning for women is more than the positive meaning.